Adverse Events of Concurrent Immune Checkpoint Inhibitors and Antiangiogenic Agents: A Systematic Review - Gao, Ling; Yang, Xi; Yi, Cheng; Zhu, Hong (Frontiers in Pharmacology, 2019)
Background: Immune checkpoint blockade has revolutionized the treatment of multiple malignancies. Currently, however, the effect is not universal, with objective response rates (ORR) of about 15–25%, and even lower for some cancers. Abnormal vasculature is a hallmark of most solid tumors and plays a role in immune evasion. Growing body of evidence suggests that vascular normalization and immune reprogramming could operate synergistic effect, resulting in an enhanced therapeutic efficacy. However, the beneﬁt of antitumor efﬁcacy must be weighed against the risk of added toxicity. In this systematic review, we summarize severe toxicity observed in such a kind of combination regimen. Methods: PubMed and EMBASE were searched for English references published up to May 31, 2019 with MeSH and keywords search terms of immune checkpoint inhibitors (ICIs) and antiangiogenic agents approved for using in solid tumos. Studies performing concomitant use of ICIs and antiangiogenic agents, and also reporting severe treatment-related adverse events (trAEs) (≥grade 3 ) were included for further analysis. Results: A total of 32 studies including a total of 2324 participants were analyzed. Limited available data suggests that both antiangiogenic monoclonal antibodies (mAbs) and tyrosine kinase inhibitors (TKIs) show potential risk of increasing treatment-related toxicity when combined with ICIs. Overall, the total incidence of severe adverse events (AEs) associated with ICIs plus mAbs (44.5%) is lower than that of ICIs plus TKIs (60.1%). However, the trAEs observed in combination therapy are mostly consistent with the known safety profiles of corresponding monotherapy, and they seem to be largely related to antiangiogenic agents, rather than a true immune-related adverse event (irAE) predominantly due to ICIs. The majority of trAEs are intervened by holding ICIs treatment and adding corticosteroids, as well as reducing dose or adjusting administration frequency of the antiangiogenic drugs. Conclusions: Concurrent use ICIs and antiangiogenic agents shows potential treatment-related toxicity. Further research is required to compare the efficacy and safety of the combination regimen and corresponding monotherapy, and identify predictive biomarkers, as well as explore dose, duration and sequencing schedule of drugs.